Layout and Industrial Efficiency: A Case Study - Santos, Fernando Charrua (2022)
In face of the pressures exerted by the globalization of the markets and the needs to meet the expectations of consumers, companies seek to improve their organizations at different levels. To meet these requirements and survive in increasingly dynamic scenarios, companies must be aware that they can not to be more static and they must adapt to gain competitive strength. In this context, the study of the industrial layout assumes an important role integrating all the elements involved in the production process. Thus, this article intends to demonstrate the relevance of the thematic study. To this objective, we present a case study layout of a manufacturing wood-based, with a proposal for improvement based on the SLP – systematic layout planning, method, combined with practical considerations and constraints, discussed here, and presents in industrial facilities.